The Medical Library Association essential guide to becoming an expert searcher : - Jankowski, Terry Ann (Neal-Schuman Publishers, 2008)
This book provides many valuable strategies and techniques in inforamtiong searching. Begin with the self-evaluation tool find out where you are on the novice-to expert continuum and then follow Jankowski through all of the components of an expert search, starting with the reference interview. A useful interview checklist and examples of librarian-user interactions will help you plan a successful, efficient search. Jankowski then guides you through the basics of search construction, offers practical guidelines for deciding what resource to start with, passes on tips and tricks from expert searchers, and reviews the usefulness of some of the most popular health science databases, like MEDLINE and PubMed, PsychInfo, CAB Abstracts, ABI/Inform, ERIC, and more